Indeksy agregatowe - błędy oceny - Wawrzynek, Jerzy (Aggregate indexes - estimate errors, 2005)
From the well known aggregate indices of price and quantity the special interest is given in this paper to the price indexes of Laspeyres (IPl), Paasche (IPp) and Fisher (IPf) as well as to their modifications. The indices IPL, IPPand IPFor their modifications are applied in several countries as the measures of the Consumer Price Index (CPI). The question under consideration is if such measures of CPI can be thought of as a practical approximation to a „true” cost-of-living index, or as a measure of the inflation for the national economy. Some considerations suggest, that the applied measures of CPI often overestimate the true cost-of-living index and the real rale of inflation in the given country. This paper characterizes the principal sources of biases occurring in the estimation of CPI, such as: commodity substitution bias, outlet substitution bias, new goods and services bias and quality adjustment bias.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1097, s. 133-146